Comprehensive Analysis of Integrated Healthcare Systems: Health Administration, Social Services, Health Insurance, Medical Secretarial Work, and Health Informatics - Lasloom , Abdullah Ali Askar; Alsharari , Yasser Salman S; Alsharari , Turki Salman S; Alazmi , Ahmad Mubarak M; Aljabbab , Bandar Mohammed H; Alkhaibari, Maryam Ibrahim S; Al-Mahri , Mohammed Misfer M; Alsaleem , Mohammad Hamad M; Alhammam , Mohammad Yahya; Al Buaybiah , Mohammed Hadi M; Albuaybiah , Hussain Hadi M; Algamedi , Ahmed Said S (Journal of Ecohumanism, 2024)
Healthcare disparities are ranked higher in integrated healthcare systems to help advocate for efficiency, effectiveness, as well as patient satisfaction with healthcare services. These systems include segments like health administration, social services, health insurance, and medical secretarial operations, as well as health informatics, they are designed to manage processes, cut out duplication, and improve patient care. Health administration delivers the facility framework for systematic organization and delivery of services, while social services offer requisite solutions to elements of social injustice and lack of access to services. Health insurance provides financial access and means requisite treatments to reach out to all sorts of population groups without exerting a lot of pressure on their pockets. Medical secretarial work improves the flow of operations since the secretary allocates appointments, records, and handles data, all of which leads to decreased human error. One essential aspect of contemporary health care that utilizes technology in decision-making, in the communication between various members of the healthcare sector, as well as in the analysis of the data collected to make predictions, minimize the incidence of medical mistakes, and improve clinical results, is health informatics. However, getting it right is rather difficult due to the challenges such as the implementation of integration, bringing about problems such as the inability to interface with other systems, lack of adequate funding, and training the workforce. EHRs and other IT innovations, combined with data analyses, show promise in eliminating these barriers and creating a stronger and more harmonized image for healthcare. These components make integrated healthcare systems advantageous in not only enhancing the quality of services they deliver but also in advancing a health delivery model that not only focuses on the health problems the patient is suffering from but also other aspects of the patient's life. It also shows the significance of extensive and proofed systems’ integration as a way to significantly change healthcare, particularly focusing on the patient-centered approach even when new challenges appear and develop in the world.